Dampak dan Pengaruh Bahasa di Media Sosial - Achmad Sohibudin Alfarisi (Pusat Riset dan Inovasi Nasional, 2023)
In this discussion, we are interested in making this study because the language used on social media tends to use slang and non-standard words that are influenced by culture, regional languages, and language absorption from other social media, therefore this study was held to provide information to people, especially adolescents, to start using good and correct Indonesian. This study aims to determine the use of Indonesian on social media. Data is obtained from status, stories, and conversations in the comments column on Twitter and Instagram that are taken randomly.